2017
DOI: 10.1016/j.molcel.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 Transcription Factors and the BAF Complex Mediate Signal-Dependent Enhancer Selection

Abstract: Enhancer elements are genomic regulatory sequences that direct the selective expression of genes so that genetically identical cells can differentiate and acquire the highly specialized forms and functions required to build a functioning animal. To differentiate, cells must select from among the ∼10 enhancers encoded in the genome the thousands of enhancers that drive the gene programs that impart their distinct features. We used a genetic approach to identify transcription factors (TFs) required for enhancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
340
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(388 citation statements)
references
References 70 publications
(92 reference statements)
48
340
0
Order By: Relevance
“…We also performed ChIP-seq for the components of the BAF chromatin-remodeling complex and observed attenuated occupancy of BRG1 and ARID1B on the GAIN sites ( Figure 5D). This is consistent with a recent report that AP1 can mediate signal-dependent enhancer selection by recruiting the BAF complex to establish accessible chromatin 46 . The effects of JUN KD on GAIN enhancer landscape were exemplified at the EGFR or CXCL8 gene loci ( Figure 5E).…”
Section: Ap1-mediated Gain Enhancer Activation Promotes Hormone Resissupporting
confidence: 93%
“…We also performed ChIP-seq for the components of the BAF chromatin-remodeling complex and observed attenuated occupancy of BRG1 and ARID1B on the GAIN sites ( Figure 5D). This is consistent with a recent report that AP1 can mediate signal-dependent enhancer selection by recruiting the BAF complex to establish accessible chromatin 46 . The effects of JUN KD on GAIN enhancer landscape were exemplified at the EGFR or CXCL8 gene loci ( Figure 5E).…”
Section: Ap1-mediated Gain Enhancer Activation Promotes Hormone Resissupporting
confidence: 93%
“…As the region around peak B has active enhancer marks, we conclude that MITF signaling is induced by activity and regulates an enhancer region in an intron of Kcnd3 leading to an activity-dependent increase in Kcnd3 expression in projection neurons of the OB. In accordance with this, stimulus dependent enhancer activity has previously been described in neurons [10,[40][41][42][43].…”
Section: Activity-dependent Increase In Kcnd3 Expression Requires Mitsupporting
confidence: 81%
“…In particular, SMARCD1 was shown to be AP-1 interacting partner in yeast two-hybrid screen (Ito et al, 2001). ATF3 was shown to physically interact with SMARCA4 (BRG1-ATPase) (Xu et al, 2011), while a more recent study showed interaction of FOS with 10 out of 15 BAF members and ability of other FOS family members (FOSD, FOSL1/2) to recruit both SMARCB1 and SMARCD1 (Vierbuchen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%